Ultra-early initiation of postoperative rehabilitation in the post-anaesthesia care unit after major thoracic surgery: case–control study. Issue 3 (24th May 2022) - Pastene, Bruno; Labarriere, Ambroise; Lopez, Alexandre; Charvet, Aude; Culver, Aurélien; Fiocchi, David; Cluzel, Armand; Brioude, Geoffrey; Einav, Sharon; Tankel, James; Hamidou, Zeinab; D'Journo, Xavier Benoit; et al.
Abstract: Background: Physiotherapy is a major cornerstone of enhanced rehabilitation after surgery (ERAS) and reduces the development of atelectasis after thoracic surgery. By initiating physiotherapy in the post-anaesthesia care unit (PACU), the aim was to evaluate whether the ultra-early initiation of rehabilitation (in the first hour following tracheal extubation) would improve the outcomes of patients undergoing elective thoracic surgery. Methods: A case–control study with a before-and-after design was conducted. From a historical control group, patients were paired at a 3:1 ratio with an intervention group. This group consisted of patients treated with the ultra-early rehabilitation programme after elective thoracic surgery (clear fluids, physiotherapy, and ambulation). The primary outcome was the incidence of postoperative atelectasis and/or pneumonia during the hospital stay. Results: After pairing, 675 patients were allocated to the historical control group and 225 patients to the intervention group. A significant decrease in the incidence of postoperative atelectasis and/or pneumonia was found in the latter (11.4 versus 6.7 per cent respectively; P = 0.042) and remained significant on multivariate analysis (OR 0.53, 95 per cent c.i. 0.26 to 0.98; P = 0.045). A subgroup analysis of the intervention group showed that early ambulation during the PACU stay was associated with a further significant decrease in the incidence of postoperative atelectasis and/or pneumonia (2.2 versus 9.5 per cent; P = 0.012). Conclusions: Ultra-early rehabilitation in the PACU was associated with a decrease in the incidence of postoperative atelectasis and/or pneumonia after major elective thoracic surgery. Abstract : We evaluated the impact of ultra-early initiation of postoperative rehabilitation after thoracic surgery. During the post-anaesthesia care unit stay (in the first hour following tracheal extubation) patients received clear fluid, respiratory physiotherapy, and ambulated under medical supervision. In our study, ultra-early rehabilitation is associated with a reduction in the incidence of postoperative atelectasis and/or pneumonia.